Allelic heterogeneity of FGF5 mutations causes the long‐hair phenotype in dogs. (6th February 2013) - Dierks, C.; Mömke, S.; Philipp, U.; Distl, O.
Summary Hitherto, the only known mutant gene leading to the long‐hair phenotype in mammals is the fibroblast growth factor 5 (FGF5). In many dog breeds, the previously discovered FGF5:p.Cys95Phe mutation appeared completely concordant with the long‐hair phenotype, but for some breeds, the long‐hair phenotype could not be resolved. First, we studied the role of the FGF5:p.Cys95Phe and FGF5:g.145_150dupACCAGC mutations in 268 dogs descending from 27 breeds and seven wolves. As these mutations did not explain all the long‐hair phenotypes, all exons and their neighbouring regions of FGF5 were re‐sequenced. We detected three novel mutations in the coding sequence and one novel non‐coding splice‐site mutation in FGF5 associated with the long‐hair phenotype. The FGF5:p.Ala193Val polymorphism was perfectly consistent with long hair in Akitas and probably in Siberian huskies, too. Dogs of the long‐hair breed Samoyed were either homozygous or compound heterozygous for the FGF5:p.Ala193Val or the FGF5:p.Cys95Phe polymorphisms respectively. The two newly detected polymorphisms FGF5:c.559_560dupGG and FGF5:g.8193T>A and the known mutation FGF5:p.Cys95Phe explained the long‐hair phenotype of all Afghan hounds analysed. An FGF5:c.556_571del16 mutation was found in one longhaired Eurasier. All long‐hair‐associated mutations follow a recessive mode of inheritance, and allelic heterogeneity was a common finding in breeds other than Akita.